2020
DOI: 10.1101/2020.06.19.161604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RUNX1 marks a luminal castration resistant lineage established at the onset of prostate development

Abstract: 22The development of castration-resistant prostate cancer is a major complication of androgen-23 deprivation therapy. However, the origin and identity of these resistant cells remains controversial. 24Here, we report that the transcription factor RUNX1 marks a specific subpopulation of proximal luminal 25 cells (PLCs), enriched in the periurethral region of the developing and adult mouse prostate, and distinct 26 from the previously identified NKX3.1 + luminal castration resistant cells. Using scRNA-seq profil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Consistent with these findings, query of a recently published single cell RNA sequencing (scRNAseq) data base from adult mouse prostate (https://shiny.cruk.manchester.ac.uk/pscapp/) detected Runx2 expression predominately in a luminal cell cluster enriched in other markers, such as Krtr8 , Krt4 , Epcam , Psca , and Wfdc2 (Lum‐D) and, to a lesser extent, in a basal cell cluster enriched in Krt5 and Krt14 . However, it was low in other luminal clusters expressing Sbp and Spink1 (Lum‐A) or Tmg4 , Nkx3.1 , and Pbsn (Lum‐B) 46 . This suggests that Runx2 is expressed in discrete luminal and basal cell populations that may function at specific stages of prostate development.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, query of a recently published single cell RNA sequencing (scRNAseq) data base from adult mouse prostate (https://shiny.cruk.manchester.ac.uk/pscapp/) detected Runx2 expression predominately in a luminal cell cluster enriched in other markers, such as Krtr8 , Krt4 , Epcam , Psca , and Wfdc2 (Lum‐D) and, to a lesser extent, in a basal cell cluster enriched in Krt5 and Krt14 . However, it was low in other luminal clusters expressing Sbp and Spink1 (Lum‐A) or Tmg4 , Nkx3.1 , and Pbsn (Lum‐B) 46 . This suggests that Runx2 is expressed in discrete luminal and basal cell populations that may function at specific stages of prostate development.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced Tgf-β signalling has been linked with the presence of quiescent epithelial progenitors in the proximal/periurethral region of the mouse prostate 25,26 . Recent single-cell studies have confirmed the enrichment of a variety of epithelial progenitors -basal, luminal proximal (LumP), and periurethral (PrU) cells -in this anatomical district, though also present at low frequency in the distal compartment [27][28][29][30][31][32] . Such cells are known to be particularly quiescent during homeostasis 33,34 , but also to exhibit extensive regenerative potential in ex-vivo assays 31,35 .…”
Section: Introductionmentioning
confidence: 91%
“…Initially, we set out to assess whether mouse prostate organoids are a representative and informative model for the study of the prostate epithelium, in light of recent discoveries on prostate cellular heterogeneity and dynamics 27,28,[30][31][32]34,38 . Considering our interest in signalling, we focused on a culture method in defined media conditions.…”
Section: Mouse Prostate Organoid Cultures Enable the Continuous Expanmentioning
confidence: 99%